Multiresidue Determination of Carbamate, Organophosphate, Neonicotinoid and Triazole Pesticides in Roasted Coffee Using Ultrasonic Solvent Extraction and Liquid Chromatography-Tandem Mass Spectrometry. (23rd November 2019) - da Silva Souza, Nicaellen Roberta; Navickiene, Sandro
Abstract: Background : A simple and effective extraction method based on ultrasonic solvent extraction and liquid–liquid microextraction (as the cleaning step) was developed to determine seven pesticide residues in roasted coffee ( Coffea arabica ) using ultra-performance LC-tandem MS. Objective : Different parameters of the method were evaluated, including solvent type and amount and sonication time. The best results were obtained using 1.0 g roasted coffee and acetonitrile (5 mL) as the extraction solvent with sonication for 15 min. The method was validated using roasted coffee samples fortified with pesticides at different concentration levels (0.1, 0.2, 0.3, and 0.5 μg/kg). Average recoveries (three replicates) ranged from 74.3 to 99.9%, with RSDs between 0.7 and 10.2%. Results : The method showed good linearity for all the pesticides studied, with correlation coefficients >0.99. The detection limits ranged from 0.02 to 0.05 μg/kg, and the quantification limit for all the compounds was 0.10 μg/kg. The proposed method was applied for analysis of the compounds in commercial coffee samples from a producer in Minas Gerais State, Brazil. No residues of the pesticides were detected in the samples. Highlights : Ultrasonic solvent extraction was effective in the analysis of pesticides in roasted coffee.